Residents’ Perceptions of the Benefits of Visitation to a Botanical Garden in South Africa - MIDDEL, Izak J.; BOUWER, Samantha C.; HERMANN, Uwe P. (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025, 2025)
The purpose of this study was to compare the perceived benefits of users and non-users of the Lowveld National Botanical Garden (LNBG) in South Africa; more specifically, users and non-users who are residents living in proximity to the Garden. The study was quantitative, descriptive, and exploratory and employed a survey research design. A structured questionnaire was used to collect data from a sample of 500 residents (including users and non-users). The results of a principal components analysis for users and non-users revealed shared factors ( i.e. benefits) between the two groups, including socio-cultural, mental well-being, leisure, and biodiversity benefits. The benefit of escapism was an additional factor elicited for the non-users. Understanding the perceived benefits has practical value in that it may serve as a foundation to develop the product offering of the LNBG and tailor the marketing communication. In this regard, repeat visitation is promoted for users, and non-users may be converted into active users. In turn, this promotes the sustainability of the Garden in an era where visitation needs to be maximized to generate tourist income to supplement limited government funds. The study is considered novel in that it has explored an under-researched population ( i.e. residents as users and non-users of a botanical garden) and an under-researched topic in a specific context, i.e. perceived benefits of botanical garden visitation in South Africa.